Group Discussion Effectiveness in Increasing Student Learning Interest in Pancasila and Citizenship Education Subjects - Suhendar, Aris; Rambe, Rahmansyah Fadlul Al Karim (Pancasila and Civics Education Journal, 2023)
Group discussion is a learning method that is carried out by students and consists of between 4 to 6 people so as to form small groups to achieve more effective learning goals. The application of this group discussion method was studied to increase student effectiveness, especially in learning activities in Civics learning subjects. The method used in this study is the literature review method by collecting data sourced from books, journals and internet sites. The results of this study are as follows: how to form appropriate discussion groups and the benefits obtained in carrying out group discussions so that they can increase students' interest in Civics subjects.